The N‐terminal subunit of vitellogenin in planthopper eggs and saliva acts as a reliable elicitor that induces defenses in rice - Jiamei Zeng; Ye, Wenfeng; Wenhui Hu; Xiaochen Jin; Peng Kuai; Wenhan Xiao; Yukun Jian; Turlings, Ted; Yonggen Lou (My University, 2023)
Vitellogenins (Vgs) are critical for the development and fecundity of insects. As such, these essential proteins can be used by plants to reliably sense the presence of insects. We addressed this with a combination of molecular and chemical analyses, genetic transformation, bioactivity tests, and insect performance assays. The small N-terminal subunit of Vgs of the planthopper Nilaparvata lugens (NlVgN) was found to trigger strong defense responses in rice when it enters the plants during feeding or oviposition by the insect. The defenses induced by NlVgN not only decreased the hatching rate of N. lugens eggs, but also induced volatile emissions in plants, which rendered them attractive to a common egg parasitoid. VgN of other planthoppers triggered the same defenses in rice. We further show that VgN deposited during planthopper feeding compared with during oviposition induces a somewhat different response, probably to target the appropriate developmental stage of the insect. We also confirm that NlVgN is essential for planthopper growth, development, and fecundity. This study demonstrates that VgN in planthopper eggs and saliva acts as a reliable and unavoidable elicitor of plant defenses. Its importance for insect performance precludes evolutionary adaptions to prevent detection by rice plants.
Keywords: defense-related signaling; elicitor; plant defense; rice planthopper; vitellogenin